Does User Search Behaviour Mediate User Knowledge and Search Satisfaction? - Yamin, Fadhilah Mat; Ramayah, T.; Ishak, Wan Hussain Wan (International Journal of Economics and Financial Issues, 2015)
Information searching in web environment is habitually tedious and challenging task. Rapid growth of web information infrastructure has led to the rapid publication of information on web environment. Too many information publish on web cause information overload problem that preclude the success of information searching. Thus, reduce the search satisfaction. This study has identified that user knowledge lead to user search behaviour and user search behaviour lead to search satisfaction. This paper discusses the investigation empirically through the search log analysis and questionnaire. The respondents were among the students at a local university in Malaysia. The findings support that the user search behaviour has a mediator effect on the relationship between the user knowledge and search satisfaction. Keywords: Search Satisfaction, User Search Behavior, User Knowledge, Web Searching, Search System. JEL Classifications: M00